Determinants of job satisfaction among food service employees in the University of the Philippines - Gatchalian, Corazon F.; Florencio, Cecilia A. (1978)
This is a study of the determinants in satisfaction of food service employees in the University of the Philippines. Using a survey questionnaire, data were obtained from the population of the University Food Service (200) composed of more than 200 administrative employees. Respondents were classified into 4 major groups according to designation and function, namely supervisors, cooks, food service workers and auxiliary employees. The over-all job satisfaction of employees and their attitude towards organizational and social sub0factors were measured using a 5 point scale of Likert type. Three main variables, personal, organizational, and social were hypothesized to be correlated with a food service employees' over-all job satisfaction. Based on median scores, results showed that supervisors were satisfied with their job content and peer group relationship. They expressed neither satisfaction nor dissatisfaction with their pay, working conditions and supervisor-subordinate relationship. Auxiliary employees were satisfied with their working conditions, and peer-group relationship. No strong sentiment of satisfaction or dissatisfaction was expressed in their pay, job content and superior-subordinate relationship. Food service employees were satisfied with their working conditions, job content, peer-group and superior-subordinate relationship. No strong sentiment of satisfaction or dissatisfaction was expressed with their pay. All groups were satisfied with their present social status. The overall job satisfaction of employees differed. Cooks were very satisfied, food service workers and supervisors were satisfied, and auxiliary employees expressed no strong sentiment of satisfaction or dissatisfaction. Using the contingency coefficient, the following sub-factors were found to be highly correlated with the overall job satisfaction: education, per capita income, length of service, job content, superior-subordinate relationship, peer-group relationship, social status, pay, and working conditions, Results showed that the personal, more than the organizational and social variables, was more correlated with a food service employee's overall job satisfaction.
Appendices: leaves 119-131.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Keywords: University of the Philippines, Quezon City. -- Food Service -- Personnel management; Job satisfaction; Employee attitude surveys -- Philippines